The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s10620-017-4851-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lumen-Apposing Metal Stents in Management of Pancreatic Fluid Collections: Are They Better Than Plastic Stents? A Systematic Review and Meta-Analysis

Abstract: LAMS seem to have excellent efficacy and safety in the management of PFCs. They may be preferred over plastic stents as they are associated with better clinical success and lesser adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 38 publications
6
82
2
Order By: Relevance
“…In the recent years, the debate regarding the appropriate stent for EUS‐guided PFC drainage has again come into the spotlight. Several systematic reviews with traditional pairwise meta‐analysis comparing metal and plastic stents in EUS‐guided PFC drainage are available . Although these data showed that metal stents improved clinical outcomes and safety compared with plastic stents, some important questions remained unaddressed, such as which metal stent improves clinical outcomes and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, the debate regarding the appropriate stent for EUS‐guided PFC drainage has again come into the spotlight. Several systematic reviews with traditional pairwise meta‐analysis comparing metal and plastic stents in EUS‐guided PFC drainage are available . Although these data showed that metal stents improved clinical outcomes and safety compared with plastic stents, some important questions remained unaddressed, such as which metal stent improves clinical outcomes and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis of 11 studies with 688 patients, Hammand et al . found LAMS to be better than multiple plastic stents in terms of clinical success and adverse events . Another recent meta‐analysis performed by Bazerbachi et al .…”
Section: Use Of Self‐expanding Metal Stentsmentioning
confidence: 98%
“…32 In a meta-analysis of 11 studies with 688 patients, Hammand et al found LAMS to be better than multiple plastic stents in terms of clinical success and adverse events. 33 Another recent meta-analysis performed by Bazerbachi et al included 41 studies with 2213 patients with WOPN. 34 WOPN resolution was more likely with SEMS compared with plastic stents (P < 0.001).…”
Section: Use Of Self-expanding Metal Stentsmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses draw conflicting conclusions while comparing plastic stents vs. metal stents for ETD of PFCs [32][33][34][35][36][37]. In three of the published systematic reviews and meta-analyses, metal stents were found superior to plastic stents for both pseudocysts as well as WON in terms of clinical success and adverse events [34,36,32]. On the contrary, two other systematic reviews and meta-analyses did not find a difference in the outcomes between metal or plastic stents [33,37].…”
Section: Endoscopic Transmural Drainage: Choice Of Stentsmentioning
confidence: 99%
“…In addition, the treatment cost (LCMS: US$12155 vs. plastic stents: US$6609) and stent related adverse events were higher in the LCMS group (32.3 vs. 6.9%, p = 0.01) [24]. Several systematic reviews and meta-analyses draw conflicting conclusions while comparing plastic stents vs. metal stents for ETD of PFCs [32][33][34][35][36][37]. In three of the published systematic reviews and meta-analyses, metal stents were found superior to plastic stents for both pseudocysts as well as WON in terms of clinical success and adverse events [34,36,32].…”
Section: Endoscopic Transmural Drainage: Choice Of Stentsmentioning
confidence: 99%